Identification of the wbtF gene as a cytotoxicity-associated factor in Francisella novicida infection - Wardhana, Dhandy Koesoemo; Shimizu, Takashi; Watanabe, Kenta; Uda, Akihiko; Watarai, Masahisa (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundFrancisella tularensis is a highly infectious Gram-negative bacterium that causes tularemia in humans and animals. It has a remarkable ability to survive and replicate within a wide range of host cells. F. novicida shares many characteristics with of F. tularensis. However, it is rarely pathogenic in humans, and its reduced virulence makes it a suitable model organism for studying F. tularensis infection. This study aimed to identify the pathogenic factors of F. novicida.MethodsUsing a novel infection model with HeLa cells expressing FcγRII (HeLa-FcγRII cells), we screened 2,232 transposon mutants of F. novicida pre-treated with antiserum containing F. novicida antibodies to find less cytotoxicity strains. The transposon insertion site was identified by sequencing, leading to the determination of the genes responsible for the attenuated cytotoxicity. Additionally, the intracellular behavior of the mutant was investigated within both HeLa-FcγRII and THP-1 cells.Results and discussionA total of thirteen mutants with attenuated cytotoxicity were isolated, and their responsible genes were identified. They are figE, slt, fopA, iglC, igID, iglF, iglI, pdpB, pdpA, ampG, wbtF, and one unnamed gene (FTN_0096). We focused on the wbtF gene. The F. novicida wild-type (WT) strain showed intracellular replication in HeLa-FcγRII and THP-1 cells, but the number of intracellular wbtF mutants decreased. The wbtF mutant could not escape from phagolysosomes in the initial phases of infection and was digested within the lysosome. The wbtF mutant was also detected in the mitochondria and the Golgi complex. The cytokine response induced by wbtF mutant was comparable to that of the WT strain. These findings indicate that wbtF is important for the intracellular replication of F. novicida.